2022
DOI: 10.1172/jci151685
|View full text |Cite
|
Sign up to set email alerts
|

15LO1 dictates glutathione redox changes in asthmatic airway epithelium to worsen type 2 inflammation

Abstract: Altered redox biology challenges all cells, with compensatory responses often determining a cell’s fate. When 15 lipoxygenase 1 (15LO1), a lipid-peroxidizing enzyme abundant in asthmatic human airway epithelial cells (HAECs), binds phosphatidylethanolamine-binding protein 1 (PEBP1), hydroperoxy-phospholipids, which drive ferroptotic cell death, are generated. Peroxidases, including glutathione peroxidase 4 (GPX4), metabolize hydroperoxy-phospholipids to hydroxy derivatives to prevent ferroptotic death, but con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(47 citation statements)
references
References 53 publications
(88 reference statements)
3
44
0
Order By: Relevance
“…The ferroptosis inducer Ras-selective lethal small molecule 3 (RSL3) significantly promotes the occurrence of lipid peroxidation and ferroptosis in IL-13-treated human airway epithelial cells (Zhao et al, 2009;Zhao et al, 2011;Wenzel et al, 2017;Zhao et al, 2020a;Nagasaki et al, 2022). In an experimental model of house dust mite-induced asthma, an association between elevated lung iron levels in airway tissue, increased ROS and lipid peroxidation and decreased GSH levels in the lungs was observed (Tang et al, 2021b), suggesting the involvement of ferroptosis in the pathogenesis of allergic asthma.…”
Section: Asthmamentioning
confidence: 99%
“…The ferroptosis inducer Ras-selective lethal small molecule 3 (RSL3) significantly promotes the occurrence of lipid peroxidation and ferroptosis in IL-13-treated human airway epithelial cells (Zhao et al, 2009;Zhao et al, 2011;Wenzel et al, 2017;Zhao et al, 2020a;Nagasaki et al, 2022). In an experimental model of house dust mite-induced asthma, an association between elevated lung iron levels in airway tissue, increased ROS and lipid peroxidation and decreased GSH levels in the lungs was observed (Tang et al, 2021b), suggesting the involvement of ferroptosis in the pathogenesis of allergic asthma.…”
Section: Asthmamentioning
confidence: 99%
“…In this issue of the JCI , Nagasaki and colleagues provide direct evidence that 15LO1-derived 15-HpETE-PE plays a role in controlling redox balance in the airway of patients with asthma, with potential pathophysiologic consequences ( 22 ). Using measures of redox balance in BAL fluids and freshly harvested bronchial epithelial cells from subjects with asthma who were enrolled in two cohort studies, the investigators found higher glutathione disulfide (GSSH) (reflecting the consumption of GSH) and lower GSH/GSSH ratios in BAL fluids from subjects with severe asthma than those with mild/moderate disease and healthy controls.…”
Section: Controlling Redox Balance In the Airwaymentioning
confidence: 99%
“…Based on studies using small interfering RNA knockdown and pharmacologic inhibition of 15LO1 in IL-13–stimulated epithelial cells, the changes involved 15LO1. Intracellular GSH levels and GSH/GSSH ratios in freshly obtained bronchial epithelial cells correlated inversely with 15LO1 expression levels but positively with the SLC7A11/15LO1 expression ratio ( 22 ). Treatment of the IL-13–stimulated epithelial cells with erastin, an inhibitor of SLC7A11 that depletes intracellular levels of GSH, induced cell death while modestly increasing expression and secretion of CCL26, periostin, and MUC5AC, each of which had previously been linked to 15LO1 activity based on ex vivo studies ( 18 , 22 , 23 , 24 ).…”
Section: Controlling Redox Balance In the Airwaymentioning
confidence: 99%
See 2 more Smart Citations